Sudden stop regimes and output: a Markov switching analysis - Andreas Bachmann; Stefan Leist (University of Bern, Department of Economics, 2013)
Sudden stops in capital inflows were a main characteristic of the emerging market crisis during the 1990's. Concerns about them have recurred in the light of recently increased global stability risk and the quantitative easing that led to substantial capital inflows in emerging economies. We add to the empirical literature that relies on a univariate approach by using a multivariate framework to assess the effect of sudden stops on economic growth and by the identification of sudden stop shocks using a Markov switching VAR and sign restrictions. The Markov switching VAR approach dates sudden stop periods comparable to the existing literature. It reveals a significant negative influence of the regime switch on economic growth that is robust across different estimation methods. Moreover, the Markov switching VAR also indicates that the reaction of macroeconomic variables to the identified shock based on sign restrictions is regime dependent.
Keywords: F32; F41; 330; sudden stops; current account; sign restriction; Markov switching